2023
DOI: 10.3389/fonc.2023.1160673
|View full text |Cite
|
Sign up to set email alerts
|

Genomic landscape and survival analysis of ctDNA “neo-RAS wild-type” patients with originally RAS mutant metastatic colorectal cancer

Abstract: BackgroundThe term “neo-RAS wild-type” refers to the switch to RAS wild-type disease in plasma circulating tumor DNA (ctDNA) from originally RAS mutant colorectal cancers. Consistently, the hypothesis to re-determine RAS mutational status in ctDNA at disease progression in RAS mutant mCRC opened to a new perspective for clinically-based selection of patients to be treated with EGFR inhibitors. Currently, the genomic landscape of “neo-RAS wild-type” is unknown. This is a prospective study aimed to investigate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Neo RAS -WT is defined as the absence of RAS mutation coupled with trunk mutations of genes such as TP53, APC, or methylated genes (Moati et al 2020 ; Nicolazzo et al 2020 , 2021 ). Nicolazzo et al reported that the most common actionable mutations detected in patients with Neo RAS -WT were PIK3CA (35.7%), RET (11.9%), IDH1 (9.5%), KIT (7%), EGFR (7%), MET (4.7%), ERBB2 (4.7%), and FGFR3 (4.7%) (Nicolazzo et al 2023 ). The prevailing notion is that concurrent genetic alterations serve as corroborative evidence for the presence of tumor DNA in the plasma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neo RAS -WT is defined as the absence of RAS mutation coupled with trunk mutations of genes such as TP53, APC, or methylated genes (Moati et al 2020 ; Nicolazzo et al 2020 , 2021 ). Nicolazzo et al reported that the most common actionable mutations detected in patients with Neo RAS -WT were PIK3CA (35.7%), RET (11.9%), IDH1 (9.5%), KIT (7%), EGFR (7%), MET (4.7%), ERBB2 (4.7%), and FGFR3 (4.7%) (Nicolazzo et al 2023 ). The prevailing notion is that concurrent genetic alterations serve as corroborative evidence for the presence of tumor DNA in the plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research suggests that temporal changes may occur in RAS status (Osumi et al 2021 ; Nicolazzo et al 2023 ). In CRC, the condition “Neo RAS wild-type (Neo RAS -WT)” refers to a situation in which a patient initially had a RAS mutation, but after treatment, the status reverted to wild-type (non-mutated).…”
Section: Introductionmentioning
confidence: 99%
“…RAS proteins are key components of the EGFR signaling pathway, and mutations in these genes lead to constitutive activation of downstream signaling, promoting cell proliferation and survival. Therefore, the presence of RAS mutations is a critical predictive biomarker, guiding treatment decisions and helping to avoid ineffective therapies. , …”
Section: Identification Of Actionable Biomarkersmentioning
confidence: 99%
“…Therefore, the presence of RAS mutations is a critical predictive biomarker, guiding treatment decisions and helping to avoid ineffective therapies. 114,115 In addition to RAS mutations, alterations in the BRAF gene, particularly the V600E mutation, are another important genetic event in colorectal cancer. BRAF mutations are observed in approximately 5−10% of colorectal cancer cases and are associated with poor prognosis.…”
Section: Identification Of Actionable Biomarkersmentioning
confidence: 99%
“…The most commonly detected actionable mutations in “neo- RAS wild-type” were: PIK3CA (35.7%), RET (11.9%), IDH1 (9.5%), KIT (7%), EGFR (7%), MET (4.7%), ERBB2 (4.7%), and FGFR3 (4.7%). OS and PFS were longer in patients with “neo- RAS wild-type” compared to those who remained RAS mutant [ 65 ]. Ciardiello et al performed a further analysis of the CAVE and VELO studies, evaluating the percentage of patients with wild-type ctDNA tumors and the association of mutational status with time since the last anti-EGFR drug administration.…”
Section: Application Of Ctdna To Guide Treatmentmentioning
confidence: 99%